2021
DOI: 10.3390/jcm10040560
|View full text |Cite
|
Sign up to set email alerts
|

Invasive and Noninvasive Nonfunctioning Gonadotroph Pituitary Tumors Differ in DNA Methylation Level of LINE-1 Repetitive Elements

Abstract: Purpose: Epigenetic dysregulation plays a role in pituitary tumor pathogenesis. Some differences in DNA methylation were observed between invasive and noninvasive nonfunctioning gonadotroph tumors. This study sought to determine the role of DNA methylation changes in repetitive LINE-1 elements in nonfunctioning gonadotroph pituitary tumors. Methods: We investigated LINE-1 methylation levels in 80 tumors and normal pituitary glands with bisulfite-pyrosequencing. Expression of two LINE-1 open reading frames (L1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 51 publications
(88 reference statements)
0
4
0
Order By: Relevance
“…SF-1 ( NR5A1 ) is a commonly accepted marker of pituitary gonadotroph cell lineage; therefore, its higher expression in group 1 of somatotropinomas requires special attention. We measured NR5A1 expression in somatotroph tumors of transcriptomic group 1 and gonadotroph PitNET samples (tumor samples from our previous investigation [ 38 ]) with qRT-PCR. This analysis showed that the range of NR5A1 expression in group 1 of somatotroph PitNETs and in gonadotroph PitNETs is similar ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…SF-1 ( NR5A1 ) is a commonly accepted marker of pituitary gonadotroph cell lineage; therefore, its higher expression in group 1 of somatotropinomas requires special attention. We measured NR5A1 expression in somatotroph tumors of transcriptomic group 1 and gonadotroph PitNET samples (tumor samples from our previous investigation [ 38 ]) with qRT-PCR. This analysis showed that the range of NR5A1 expression in group 1 of somatotroph PitNETs and in gonadotroph PitNETs is similar ( Figure 5 B).…”
Section: Resultsmentioning
confidence: 99%
“…SF-1 ( NR5A1 ) is a commonly accepted marker of pituitary gonadotroph cell lineage, therefore, its higher expression in group 1 of somatotropinomas requires special attention (Figure 4). We measured NR5A1 expression in somatotroph tumors of transcriptional group 1 and gonadotroph PitNET samples (tumor samples from our previous investigation (Rusetska et al , 2021)) with qRT-PCR. This showed that the range of NR5A1 expression in group 1 somatotroph PitNETs and gonadotroph PitNETs is similar (Figure 4B).…”
Section: Resultsmentioning
confidence: 99%
“…The mechanisms responsible for their genesis and progression into more aggressive forms remain unknown. 83 , 84 , 85 In the aggressive pituitary adenoma type, miR-128-3p is one of the few microRNAs suppressed compared with control tissues. Its reintroduction into pituitary cancer cells inhibits their colony-forming ability and invasiveness in vitro .…”
Section: Mir-128-3p In Malignancies Of the Cnsmentioning
confidence: 99%